Hippocampal cell proliferation regulation by repeated stress and antidepressants - Chen, Hu; Pandey, Ghanshyam N; Dwivedi, Yogesh (Neuroreport, 2006)
A recent hypothesis suggests reduced hippocampal neurogenesis in depression. Here, we examined cell proliferation in the dentate gyrus and the subventricular zone of rats given repeated stress, a paradigm that prolongs learned helplessness behavior, and whether antidepressants modulate the learned helplessness-associated altered cell proliferation. Decreased cell proliferation, number of clusters, and cells/cluster were noted in the dentate gyrus, but not in the subventricular zone, of learned helplessness rats. Both fluoxetine and desipramine reversed the learned helplessness behavior and increased the cell proliferation and the number of clusters in learned helplessness rats; only fluoxetine did so significantly. Both fluoxetine and desipramine significantly increased the number of cells/cluster. Our results suggest modified hippocampal neurogenesis in prolonged depression and in the mechanism of antidepressant action.